Особливості перфекціонізму та його взаємозв’язки із заздрісністю у засуджених чоловіків та жінок - Мохорєва, О. М.; Mokhorieva, O. M.; ORCID: http://orcid.org/0000-0002-9420-2847 (Вісник Львівського університету. Сер.: Психологічні науки. - 2022. - Вип.14. - С. 32-39, 2022)
Розглянуто актуальність дослідження феномену заздрісності та перфекціонізму. Заздрісність має тенденції неусвідомленого функціонування в особистості, породжуючи різні модифікації проявів, що забезпечені активізацією механізмів психологічного захисту, і може призводити до порушень, розладу, ненависті і деструкції в людських відносинах. Зазначено, що під феноменом перфекціонізму розуміють прагнення суб’єкта до досконалості, високі особисті стандарти, прагнення людини доводити результати будь-якої своєї діяльності до найвищих стандартів, потребу в удосконаленні продуктів своєї діяльності. Досліджено взаємозв’язки заздрісності з перфекціонізмом у засуджених чоловіків та жінок.

The article considers the relevance of the study of the phenomenon of envy and perfectionism. It is noted that it is a complex psychological phenomenon, which is characteristic of human nature, determined by various factors, has a variety of forms and degrees of expression. Envy has tendencies of unconscious functioning in the individual, giving rise to various modifications of manifestations provided by the activation of psychological protection mechanisms, and can lead to violations, disorder, hatred and destruction in human relations. Attention is focused on the main mechanisms of envy formation, among which internalization, the mechanism of causal delusion, the mechanism of social comparison, and the mechanism of categorization are distinguished. As for the phenomenon of perfectionism, in recent decades it has become the subject of intensive empirical research in the field of psychological science. It is noted that the phenomenon of perfectionism is understood as the subject’s desire for perfection, high personal standards, a person’s desire to bring the results of any of his activities to the highest standards, the need to improve the products of his activity. The multidimensional scale of perfectionism by P.L. Hewitt, G.L. Flett (adapted by I.I. Grachova) was used to study the features of perfectionism and its relationships with envy in men and women. According to the definition of the authors of this scale, perfectionism is considered the desire to be perfect, flawless in everything.. In the course of the conducted research on the comparison of perfectionism and its relationships with envy, it was found that in a group of women, the growth of socially attributed perfectionism is accompanied by an increase in both types of envy, while in men, all types of perfectionism turned out to be separate from the feeling of envy. The grounds for the hypothesis about the relationship between envy and perfectionism were considered: both psychological constructs are associated with hostility. The hostile component of envy is un derstood as a momentary defensive reaction arising in response to frustration and shame caused by the experience of inferiority in the face of unflattering social comparisons; envy is triggered by disappointing social comparisons.

Рассмотрена актуальность исследования феномена зависти и перфекционизма. Завистливость имеет тенденции неосознанного функционирования в личности, порождая различные модификации проявлений, обеспеченные активизацией механизмов психологической защиты, и может приводить к нарушениям, расстройству, ненависти и деструкции в человеческих отношениях. Отмечено, что под феноменом перфекционизма понимают стремление субъекта к совершенству, высокие личные стандарты, стремление человека доводить результаты любой своей деятельности до самых высоких стандартов, потребность в совершенствовании продуктов своей деятельности. Исследованы взаимосвязи завистливости с перфекционизмом у осужденных мужчин и женщин.
Characteristics of perfectionism and its relationship with envy in convicted men and women
Мохорєва, О. Особливості перфекціонізму та його взаємозв’язки із заздрісністю у засуджених чоловіків та жінок / Олена Мохорєва // Вісник Львівського університету. Сер.: Психологічні науки. - 2022. - Вип.14. - С. 32-39. - DOI https://doi.org/10.30970/PS.2022.14.4.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Юридична психологія. Legal psychology. Юридическая психология; Україна. Ukraine. Украина; заздрісність; jealousy; завистливость; заздрість; envy; зависть; перфекціонізм; perfectionism; перфекционизм; засуджені жінки; convicted women; осужденные женщины; засуджені чоловіки; convicted men; осужденные мужчины